ORU analyses of immigrant earnings in Australia, with international comparisons - Barry R. Chiswick; Paul W. Miller (Institute for the Study of Labor (IZA), 2009)
This paper examines the way immigrant earnings are determined in Australia. It uses the overeducation/required education/undereducation (ORU) framework (Hartog, 2000) and a decomposition of the native-born/foreign-born differential in the payoff to schooling developed by Chiswick and Miller (2008). This decomposition links overeducation to the less-than- perfect international transferability of immigrants' human capital, and undereducation to favorable selection in immigration. Comparisons are offered with findings from analyses for the US and Canada to enable assessment of the relative impacts of favorable selection and the limited international transferability of human capital to the lower payoff to schooling for the foreign born. The sensitivity of the results of the decomposition to several measurement issues is assessed.
urn:nbn:de:101:1-20091014979
Keywords: F22; I21; J24; J31; J61; 330; Immigrants; schooling; occupations; earnings; rates of return; selectivity; skill transferability; ORU analysis; Migranten; Einkommen; Überqualifikation; Bildungsertrag; Lohndifferenzierung; Schätzung; Australien; Vergleich; USA; Kanada